Electrochemical investigation of substituted pyranopyrazoles adsorption on mild steel in acid solution - Yadav D.K.; Quraishi M.A. (My University, 2025)
Four substituted pyranopyrazole derivatives (PPZs) were synthesized and their effects on the electrochemical behavior of mild steel in 1 M HCl were investigated using gravimetric measurements, Tafel extrapolation method, linear polarization resistance (LPR), and electrochemical impedance spectroscopy (EIS). Tafel polarization measurements revealed that these compounds effectively suppressed both the anodic and cathodic processes of mild steel corrosion in acid solution and acted as mixed-type inhibitors. Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX) examinations of electrode surface confirmed the existence of adherent layer of inhibitor on electrode surface. The UV-visible absorption spectrum of inhibitor solution containing mild steel indicated the formation of Fe-PPZ complex. Quantum chemical calculations have been used to evaluate the structural, electronic, and reactivity parameters of the selected pyranopyrazole derivatives in relation to their inhibition action. © 2012 American Chemical Society.